CONTEMPORARY TRENDS IN INSURANCE UNDER MARTIAL LAW - Kononenko, Ganna I. (Journal of Strategic Economic Research, 2023)
The article attempts to provide insights into contemporary issues, risks and challenges faced by insurance companies in the wartime settings. It is observed that the Russian military aggression against Ukraine has caused huge losses and large-scale destruction to infrastructure, property and the national economy overall. Thus, the natural desire to protect property to prevent loss or damage that may occur due to military actions of the invaders is quite understandable. It is argued that insurance is a universal tool to mitigate risks. However, the war and hostilities have had drastic effects to the insurance market operation. It is noted that in each insurance company, the structure of insurance contracts is of an individual character as to the occurrence based insurance events resulting from military operations differ in each specific case and therefore, each such contract requires careful consideration of all its provisions. In the context of this study, a focus is put that in case of a natural disaster (any cataclysm) when property is damaged, the insurance contract will not cease to apply and will act as before the war. It is argued that the fact of imposition of martial law is not to be a reason to refuse customers in their insurance claims. The findings demonstrate that cause-and-effect relationship between the war / military actions and the losses incurred is the fundamental factor, therefore the occurrence of an insurance event on the temporarily occupied areas since February 24, 2022 cannot be the ground for denying a customer’s insurance claim for compensation. The study suggests that the government insurance policy should be focused towards effective implementation of a range of various actions that will help support the industry growth (tax burden reduction, improving regulations, etc.). Apart from the above, a conclusion is made that insurance contracts remain legally valid regardless of whether military operations are being conducted in Ukraine or not. The study has revealed that some insurance companies refuse to provide indemnity for military / war risks, and also exclude hostile zones from insurance coverage, which in turn might translate in lawsuits against insurance companies. It is also observed that currently, if an insurance company’s customer has a valid insurance contract, the imposition of martial law and active hostilities in Ukraine cannot be a barrier to respond to insurance claims and insurance payments. According to the results of the research, it is concluded that insurance companies should continue to operate effectively and enhance insurance products, simplify the procedures for concluding contracts as well as offer the opportunity to customers to sign insurance contracts online.